0480 Rapid Eye Movement Period Apnea Contribute to Peripheral Arterial Stiffness in Obstructive Sleep Apnea Syndrome. (27th April 2018) - Liao, F; Tsai, W; Ho, C; Chen, J; Lin, C
Abstract: Introduction: Obstructive sleep apnea (OSA) contributes to cardiovascular diseases, including arterial stiffness. The association between OSA and peripheral arterial stiffness indices remains controversial. Methods: This study recruited 275 patients who were referred for sleep apnea study. Arterial stiffness was assessed by peripheral compliance index (CI) and central pulse wave velocity derived from digital volume pulse (PWV-DVP) by photoplethysmography. Overnight polysomnography and autonomic nerve system function tests were also conducted. Results: A total of 275 patients (170 men) were recruited. Most were middle-aged and overweight. Most patients (112/275, 40.7%) had rapid eye movement (REM)-predominant OSA. The CI was significantly correlated with the apnea-hypopnea index (AHI) ( R = -0.132, P = 0.029) and AHI-REM ( R = -0.170, P = 0.005) and AHI Non-REM ( R = -0.122, P = 0.043). Among models and variable used to predict CI, only male sex ( B = -0.708, P = 0.007) and AHI-REM ( B = -0.010, P = 0.033) were independent predictors of CI. An increase in the interquartile range of AHI-REM was associated with a 9.6% decrease in CI. Conclusion: AHI-REM was independently correlated with a peripheral arterial stiffness index, CI. AHI-REM may be a suitable surrogate marker for predicting peripheral arterial stiffness in OSA patients. Support (If Any): nil.